More Dangerous Than Many a Pamphlet or Propaganda Book: The Ukrainian Canadian Left, Theatre, and Propaganda in the 1920s - Luciuk, Kassandra (Labour / Le Travail)

(untitled) (Canadian Committee on Labour History, 2019)
For Ukrainian Canadian leftists, the 1920s represented a golden age of domestic cultural production. The strict hierarchy that constituted the communist movement in the 1930s was not yet extant, and the realm of possibilities was limited only by the imagination of the organization itself. The material produced in this period was neither crass agitprop nor cheap melodrama. Rather, it was bottom-up expressions of proletarian high culture and organic reflections of the social, economic, and political realities that constituted the experiences of Ukrainian progressives in Canada. As such, in the 1920s, the theatre served as the movement’s most effective vehicle for political propaganda and ethnocultural instruction.